Determination of validamycin A in agricultural food samples by solid-phase extraction combined with liquid chromatography–atmospheric pressure chemical ionisation–tandem mass spectrometry. (15th February 2015) - Wang, Chuanxian; Zhang, Zhigang; Shen, Yan; Tian, Zhengan; Xu, Dunming; Han, Chao
Highlights: Validamycin A LC–APCI–MS/MS analysis for the first time. There are few reports on the determination of validamycin A in food. Validamycin A determination in agricultural food matrix. Abstract: For the first time, a rapid, sensitive and accurate liquid chromatography–atmospheric pressure chemical ionisation–tandem mass spectrometry (LC–APCI–MS/MS) method was developed for determination of validamycin A in agricultural food samples (rice, agaric, almond, cabbage, green onion, carrot, tomato, cucumber and spinach). The validamycin A residue was extracted with methanol–water (9/1, v/v) or methanol by vortex, and a HLB solid-phase extraction cartridge was used for cleaning up the extracts. LC–APCI–MS/MS data acquisition was carried out in multiple reaction monitoring (MRM) mode. A series of matrix-matched calibration solutions ranging from 2.5 to 50 ng mL −1 were used to record calibration curve. The limit of quantification (LOQ) was 10 μg kg −1 . The average recoveries, measured at three concentrations levels (10.0, 50.0, 100.0 μg kg −1 ) were in the range 83.5–109.6%. The proposed method offers the best sensitivity and specificity for the routine analysis of validamycin A in agricultural food samples.